Analyses of heat recovery devices in the HVAC system in an operating theatre in the tropics - Yau, Y.H. (SAGE Publications, 2010)
The air-conditioning system is the major electricity consumption for the non-domestic buildings. A significant part of energy savings can be achieved if heat recovery technologies such as run-around coils, plate-to-plate heat exchangers, heat recovery wheels and heat pipe heat exchangers are incorporated into the ACMV system of these buildings. Nondomestic buildings, such as hospitals, expense even more energy as the supply of fresh air into the space is deemed necessary. For example, air must be changed at least 25 times hourly and recirculation of RA is prohibited for the operating theatres. Therefore, an operating theatre of a hospital in a tropical climate country was chosen for this research. The performance of the existing air-conditioning system has been thoroughly studied to investigate the potential in energy savings in the building. The transient system simulation program (TRNSYS) was used to analyse the air-conditioning system incorporated with heat recovery devices. Generally, there are eight heat recovery systems analysed using TRNSYS, which divided into two groups: the heat recovery ventilating system and heat recovery dehumidification system. The energy savings, payback period, dehumidification enhancement, stability of indoor air conditions and preventing the cross contamination, for each of the systems, were analysed in comparison to each other. Based on this study, it is recommended that the heat recovery systems should be installed to enhance moisture removal and reduce energy usage of HVAC system operating in hospitals. Practical application: The good amount of technical information of real application conducted on heat recovery devices installed in HVAC systems in operating theatres in the tropics could be used as a comprehensive guide for building services engineers and researchers who are intending to apply heat recovery devices as `coolness' recovery and dehumidification devices in HVAC systems operating in tropical countries. Practical application: The good amount of technical information of real application conducted on heat recovery devices installed in HVAC systems in operating theatres in the tropics could be used as a comprehensive guide for building services engineers and researchers who are intending to apply heat recovery devices as `coolness' recovery and dehumidification devices in HVAC systems operating in tropical countries.